Making a Small Market Thrive : Recommendations for Efficiency Gains in the Latin American Air Cargo Market - Serebrisky, Tomás; Schwartz, Jordan; Pachón, María Claudia; Ricover, Andrés (World Bank, Washington, DC, 2014)
Air cargo origin destination flows in the Latin America and the Caribbean (LAC) region are heavily concentrated in the largest economies of South America and Mexico. With 32.7 percent of the airfreight moved to, from, and within the region, Brazil is the largest cargo market, followed by Colombia and Mexico, with 17.9 percent and 16.0 percent, respectively. The relatively small size of the air cargo market in LAC can be explained by: (i) low levels of demand for air cargo services (supply responds adequately to a low demand for air cargo services in/from LAC), or (ii) restrictions to a properly functioning market that impede the air cargo market to reach its full potential. The analysis carried out for the preparation of this paper indicates that the low levels of demand is the most reasonable explanation for the small size of the LAC air cargo market. There is room to improve some regulations which would make the air cargo market work more efficiently and probably at lower costs, but the size and diversity of the market will not significantly change as a result. Airport infrastructure quality fairs well overall, although some isolated issues exist in certain airports in LAC. Infrastructure limitations were evaluated through a survey conducted by an association of LAC airlines (ALTA). The results of the survey show that even the worst rated airports received an acceptable score in absolute terms. Policies aimed at reducing operating costs and related to soft constraints should also be implemented paperless customs procedures, improved security in airport premises and streamlining of custom inspection processes.